2006
DOI: 10.1177/0092055x0603400104
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Social Science Reasoning and Quantitative Literacy: The Role of Collaborative Groups

Abstract: In this paper, we discuss ways collaborative research groups can be used and what students appear to learn about social science reasoning and quantitative literacy from such groups. Data are from field observations, pre- and post-semester surveys in both collaborative and traditional courses, end of the semester student comments, and student work on semester-long group-based projects. The findings illuminate teaching and learning processes, cognitive and personal learning outcomes, and remaining challenges. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Furthermore, students may benefit from peer explanations because they can describe the concepts using similar language (Caldwell, 2007;Nicol & Boyle, 2003). However, students may not necessarily appreciate collaboration, particularly if they have had negative previous experiences with group work (Caulfield & Hodges Persell, 2006). If they have negative perceptions about collaboration, then it can influence their attitudes toward the course content (Slusser & Erickson, 2006).…”
Section: Collaborative Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, students may benefit from peer explanations because they can describe the concepts using similar language (Caldwell, 2007;Nicol & Boyle, 2003). However, students may not necessarily appreciate collaboration, particularly if they have had negative previous experiences with group work (Caulfield & Hodges Persell, 2006). If they have negative perceptions about collaboration, then it can influence their attitudes toward the course content (Slusser & Erickson, 2006).…”
Section: Collaborative Learningmentioning
confidence: 99%
“…Therefore, we made no predictions about the directionality of possible differences. In light of previous research that has shown that negative feelings toward collaboration can erode its value (Caulfield & Hodges Persell, 2006;Slusser & Erickson, 2006), the second research question was: "What are students' perceptions about shared and individual clicker use?" Although we expected the students to have positive reactions to the use of clickers generally, we made no predictions as to whether they would express a preference for shared or individual clicker use.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Empirical evidence on strategies for improving quantitative literacy suggests that teaching practices that engage students in hands-on activities are more effective. These include asking substantive questions relevant to students' lives (Atkinson, Czaja, and Brewster 2006;Burdette and McLoughlin 2010;Lindner 2012;Stroup et al 2004), having students collaborate in groups 867996T SOXXX10.1177/0092055X19867996Teaching SociologyStojmenovska et al (Caulfield and Caroline 2006), write reflective learning journals (Denton 2018) or collect their own data (Strangfeld 2013), and using computers for working with data (Wilder 2009).…”
mentioning
confidence: 99%
“…Previous research has argued the benefits of cooperative learning (Ruiz-Primo et al 2011) as motivating (Bartle, Dook and Mocerino, 2011) and confidence-building (Caulfield and Persell, 2006). However, cooperative learning needs to be characterized by group member interdependence, a sense of accountability and an understanding among students as to the purposes and potential benefits this mode offers in terms not only of content-area understanding, but also social and communicative skills (Johnson et al 1981).…”
Section: Discussionmentioning
confidence: 99%